Assisting the facilitators -- interface design and telematic support for IT-based assistive technology. - Zagler WL; Panek P (Technology & Disability, 1999)
When it comes to designing assistive technology, rehabilitation engineers have to bear in mind that the disabled person is not the only person to be addressed. Quite often a facilitator, who can be a family member, a professional carer, a therapist or a teacher, is the key person to ensure function and efficiency of the assistive technology in use. These facilitators are seldom experts in rehabilitation technology or computer programming. To exploit the high potential of this highly motivated but often inexperienced group we seek to tackle this problem from two sides. The first approach has been realized in a PC-based environmental control and communication system, which we have equipped with three different and dedicated user interfaces: one for the disabled person, another for the facilitator and a third one for the integrator--the knowledgeable person responsible for the first set-up of the system. The paper describes the goals, benefits and success of this multiple-user dedicated interface design. The second approach presently is the topic of a European Union R&D project, by which a concept for telematic service provision is developed and will be put to trial in 1999. Users of PC-based assistive technology and their facilitators will be equipped with an easy to use telematic link by which a service provider can be contacted. The service link consists of speech and video telephony, remote controlling and monitoring the clients PC and several diagnostic and maintenance features for updating software and troubleshooting.